Comparison of PED Flex and Lattice flow diverter in the treatment of unruptured intracranial aneurysms - Xuexian, Zhang; Xuerou, Meng; Yuanjin, Ma; Bin, Xiong; Wenqiu, Pan; Wei, Zhao; Ruidong, Wang (Frontiers in Neurology, 2025)
Background and objectiveFlow diverters (FDs) are widely used in the treatment of intracranial aneurysms (IAs). The Lattice flow diverter (LFD) is a novel FD developed in China, specifically designed for large or giant IAs. Currently, few studies have compared various FDs in the treatment of these conditions. This study endeavors to contrast the safety and efficacy of the Pipeline Flex embolization device (PED Flex) and LFD in the treatment of unruptured intracranial aneurysms (UIAs).MethodsThis study retrospectively reviewed cases of UIAs managed with PED Flex or LFD at the Department of Interventional Radiology, Kunming Medical University’s First Affiliated Hospital from March 2022 to September 2024. We analyzed demographic characteristics, aneurysm features, medical history, complications, aneurysm occlusion, and clinical outcomes.ResultsThe study cohort consisted of 99 patients with 99 aneurysms, including 48 treated with PED Flex and 51 with LFD. The median follow-up duration was 9 months for both groups. Rates of complete aneurysm occlusion (81.3% vs. 78.4%, p = 0.727), successful aneurysm occlusion (87.5% vs. 86.3%, p = 0.857), and complication rates (2.1% vs. 3.9%, p = 0.727) did not differ significantly between the groups. Similarly, rates of in-stent stenosis (ISS) (14.6% vs. 11.8%, p = 0.678) and positive clinical outcomes were comparable.ConclusionOur preliminary findings indicate that compared with PED Flex, the new domestic LFD has similar safety and effectiveness in treating UIAs. It is a new option for treating intracranial aneurysms and may have broad application prospects.